Beneficence and Non-maleficence at the End of Life: The Case of Artificial Nutrition and Hydration - Pinho-Reis, Cíntia (2019)
With advances of modern medicine and technological knowledge, the number of people with chronic and progressive diseases has increased. The treatment options have also increased so hastening death has become possible. When it is necessary to make a decision about artificial nutrition and hydration in patients in palliative care, these same decisions present complex ethical dilemmas involving the principles of beneficence and nonmaleficence.